Impact of Health Education on Epistaxis First Aid Knowledge among Primary School Teacher in Penjaringan District - Meidiana Lie; Soegianto Ali (Institute for Research and Community Services, 2019)
Epistaxis is defined as bleeding of the nose that frequently occurs in children. Although epistaxis is not a serious condition, the correct first aid management is necessary to prevent the complication. Primary school teachers take the role of parents in school, therefore they are expected to know the right first aid management of epistaxis. It is expected that health education on epistaxis will increase the knowledge of first aid management on epistaxis. This training aims to know the impact of health education on the knowledge of epistaxis first aid management among primary school teachers in Penjaringan District. The training was evaluated in the pre and post intervention. The respondents were five primary school teachers from elementary schools in Penjaringan Districts, North Jakarta. Data were collected by questionnaire based interview taken from Dr.Nymbaka O. Kevin M. Med ENT, Head & Neck Surgery Resident “An Assessment of Knowledge, Attitude and Practice in First Aid Management of Epistaxis” before and after the health education. The results showed that there was an increase of number of teacher with good level of knowledge on epistaxis management from 5,3% to 96,1% after the health education. The paired t-test analysis shows the increase was statistically significant. Evaluation of the training confirmed that epistaxis health education improved the knowledge of epistaxis first aid management among primary school teachers in Penjaringan District.